2018
DOI: 10.3389/fpsyg.2018.00342
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Specific Self-Efficacy Scale in Adherence to a Gluten-Free Diet

Abstract: The aim of this study was to develop a scale to assess the levels of specific self-efficacy in order to enhance adherence to a gluten-free diet and the life quality of celiac patients. Celiac disease is a chronic small intestinal immune-mediated enteropathy precipitated by exposure to dietary gluten in genetically predisposed people. The only treatment is a strict lifelong gluten-free diet. Within the framework of Social Cognitive Theory, expectation of self-efficacy is understood as the degree in which a pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Considering regression analysis, it seems that specific rather than general self-efficacy plays a role in predicting adherence to a GFD, which is in line with previous research [27], and which emphasizes the need to measure control beliefs more specifically rather than in a general way. The results in our study support the idea, as in other studies [27,29,39], that the areas in which people with CD are less confident are "traveling," "shopping," and "eating out".…”
Section: Self-efficacysupporting
confidence: 91%
See 2 more Smart Citations
“…Considering regression analysis, it seems that specific rather than general self-efficacy plays a role in predicting adherence to a GFD, which is in line with previous research [27], and which emphasizes the need to measure control beliefs more specifically rather than in a general way. The results in our study support the idea, as in other studies [27,29,39], that the areas in which people with CD are less confident are "traveling," "shopping," and "eating out".…”
Section: Self-efficacysupporting
confidence: 91%
“…This research shows that specific self-efficacy, adherence to the GFD as well as risk perception, time since diagnosis, and age play an important role in the HRQoL of patients with CD. Results show that it is self-efficacy, when specifically measured, that best predicts adherence to the GFD and the resulting HRQoL [27,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FNS is, at the same time, closely linked to adverse eating patterns and reduced dietary quality, which is related to an increased risk of obesity and non-communicable diseases which was proven in the recent study of Sarin et al [24]. It must be emphasized, that in literature there are also other tools to measure traits related to the quality of life of CD patients and other aspects, such as the Celiac Dietary Adherence Test (CDAT) [53,54], Celiac Disease Self-Efficacy (Celiac-SE) questionnaire [55] or Celiac Disease Questionnaire (CDQ) [56]. In spite of the fact that the FNS and CD-FAB are different tools, it must be emphasized that common elements exist here, which are associated with identifying eating attitudes and behaviors, as it was demonstrated that food neophobic individuals have not only a tendency to avoid new food products, but also to dislike them [57] or to evaluate them in a negative way [18].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a RCT found that six months of psychological counselling improved GFD adherence and reduced depression in CD patients with depression at baseline [ 89 ]. While no studies exist that support or repute our findings that a lower proportion of children achieved strict adherence than adults, practical tools have been shown to promote self-management, dietary adherence and well-being in children and adolescents with CD [ 90 ]. Hence, the development of both standardised measurement methods and tools to promote dietary adherence would be useful for future research, as well as patient management.…”
Section: Discussionmentioning
confidence: 99%